Anti-inflammatory Activity of Bajakah Stem (Spatholobus littoralis Hassk.) Ethanolic Extract in Carrageenan-Induced Paw Edema Mice - Diah Wulandari Rousdy; Elvi Rusmiyanto Pancaning Wardoyo; Siti Ifadatin (UIN Sunan Gunung Djati Bandung, 2022)
Bajakah tampala plant (Spatholobus littoralis Hassk.) has been used for traditional medicine by the Kalimantan Dayak tribe in the treatment of cancer. This study aimed to find out the potential of ethanol extract of the stem of Bajakah tampala (Spatholobus littoralis Hassk.) as an anti-inflammatory agent in carrageenan-induced mice. The method used was a Completely Randomized Design with five treatments and five replications. The treatments consisted of a water-treated mouse as a negative control, sodium diclofenac 30,8 mg kg-1 as a positive control, and an extract of bajakah dose 2.5; 250; 1250 mg kg-1 BW. The dose of bajakah extract was given orally one hour before carrageenan induction. The inflammation induction used the Winter method by injecting 0.15 ml of 2% carrageenan suspension into the soles of mice. The diameter of edema was measured for 210 minutes. The results showed that the diameter of the mice soles showed a significant increase in all groups after the carrageenan injection. The value of AUC (Area Under the Curve) of bajakah extract dose (2.5; 250; 1250 mg kg-1) from the 150th minute to the 210th minute did not show significant differences from one another. The sodium diclofenac as positive control gave the lowest total AUC value of 236 mm.minute, followed by bajakah extract at a dose of 2.5 mg kg-1 BW of 239.22 mm.minute. The calculation results of the percentage of the inflammation inhibition showed that the administration of ethanol extract of the stem of Bajakah, Spatholobus littoralis, at the lowest dose of 2.5 mg kg-1 BW provide the best inflammation inhibition with 19.21% inhibitory value, nearly approaching the positive control of diclofenac sodium with an inhibitory value of 21.53%.